Alliances in the shadow of conflict - Changxia Ke; Kai A. Konrad; Florian Morath (Center for Economic Studies and ifo Institute (CESifo), 2012)
Victorious alliances often fight about the spoils of war. This paper presents an experiment on the determinants of whether alliances break up and fight internally after having defeated a joint enemy. First, if peaceful sharing yields an asymmetric rent distribution, this increases the likelihood of fighting. In turn, anticipation of the higher likelihood of internal fight reduces the alliance's ability to succeed against the outside enemy. Second, the option to make non-binding declarations on non-aggression in the relationship between alliance members does not make peaceful settlement within the alliance more likely. Third, higher differences in the alliance players' contributions to alliance effort lead to more internal conflict and more intense fighting.
Keywords: D72; D74; 330; conflict; contest; alliance; endogenous internal conflict; hold-up problem; non-aggression pact; experiment; Konflikt; Bündnissystem; Sunk Costs; Test